Estimation of the quality of life in patients with prostate cancer hospitalized during radical radiotherapy treatment. Part II - Nowicki, Andrzej; Staniewska, Jadwiga; Tesmer, Izabela (Contemporary Oncology/Współczesna Onkologia, 2007)
Background : The prostate cancer is the most frequent tumor of the urinary – sexual system among men. The choice of therapy depends mainly on side effects. Aim of study : The detailed (pertaining to an organ) assessment of quality of life in patients with prostate cancer during the radical radiotherapy was a main goal of this work. Material and methods : The prospective surveys were done among patients who have undergone treatment in the Centre of Oncology in Bydgoszcz since August till December 2006 year. Our survey includes 26 men at age 53-86 (median 69) with the diagnosis of prostate cancer treated with conformal radical radiotherapy under hospital conditions. The treatment was run using photons X produced by a linear accelerator, 5 times a week with 2 days pause on average. Average overall time of treatment was 6.5 weeks (which made 33 fractions on average). An average dose of radiation was 66 Gy per patient. Standard questionnaire EORTC QLQ - C25 addressed to particular disease. Results : Radiotherapy seriously disturbed function of the urinary tract from among of other problems observed in prostate cancer treatment. (median point-rate was 1.65 for group A1 and 2.01 for A2). Very frequent urinating during day time was fundamental problem at the end of treatment period (often and very often in 30.77 % of patients) and during night time (often in 38.46 % of patients and very often in 30.77%). Hurrying to the toilet at the moment of necessity of urinate caused problems at the end of treatment occurred sometimes, often and very often in 30.77% of patients. Frequent getting up to the toilet during sleep time often disturbed rest in 30.77% of patients and very often in 15.38% at the end of treatment period. Problems with urinating sometimes limited daily activities in 26.92% of men and very often in 23.08 % of men in group A2. Radiotherapy also seriously disturbed function of guts, median point-rate was 1.17 for group A1 and 1.47 for group A2. Problems with intestines connected with defecation were very essential in the end of therapy (sometime 26.92% of patients, often – 19.23%). The presence of blood in excrements was sometime observed in 19.23% patients. Flatulence was sometime observed in 46.15% of men and often in 11.54%. Conclusions : Radiotherapy made worse functions of the urinary system and intestines significantly, however did not disturb considerably any sexual functions during the early treatment period.